THE EMERGENCE OF EMOTION, ITS MAIN STATES AS INTERPRETED BY PSYCHOLOGIST CARROLL ELLIS IZARD (Scientific journal of the Fergana State University, 2024)
This article provides information about the experiences of a person, the emergence of feelings, their main forms and situations, arising from the relationship to things and events in reality, to people and to oneself, as well as the scientific views of scientists in this regard. An opinion about the division of feelings into different forms such as emotion, effect, mood, strong excitement (stress state) and the organization of the emotional-expressive sphere of a person, the regulation of human behavior, the expression of complex and multifaceted relations between people as a living source of knowledge. - comments were studied and reacted to.